THE IMPACT OF DRAINAGE NETWORK CONDITION ON THE MINERALIZATION OF WATER (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The use of manifold-drainage water for the purpose of irrigation is first of all conditioned by its mineralization and quality. Prognosis on the mineralization of drainage water is made depending on the depth of the ground water level bedding. The expected mineralization after the water in manifolds, drainage network and water-collector is mixed, has also been prognosticated. According to the estimates, the cleaning of the manifold-drainage network (reducing of the ground water level) of Ararat valley will not significantly affect the mineralization and quality of the water and it will still be good for irrigation. The overall flow of that type of water during the vegetation period is approximately 20-25 m3/s (400-500 mln m3).
Keywords: manifold-drainage water; drainage water; ground water level bedding; mineralization of water